Essays on the Modeling of Risks in Interest-rate and Inflation Markets - Allan Sall Tang Andersen (Copenhagen Business School (CBS), 2011)
The topic of this thesis is the modeling of risks in interest-rate and inflation markets. Interest-rate risk is an important issue to investors. For instance, according to BIS (2010) the notional value of over-the-counter interest-rate derivatives markets is 465,260 billion US-dollar. This corresponds to 77 percent of the notional of the entire OTC derivatives market. Thus interest-rate derivatives is at the back-bone of the financial markets. According to ISDA (2009) 83 percent of Fortune 500 companies report using interest-rate derivatives in their risk management. Furthermore, many mortgage-based loans and pension contracts contain either explicit or implicit interest-rate options. Thus a better understanding of the interest-rate derivative markets, and the risk associated with the traded products is of great value, both to financial and non-financial companies as well as individuals....
hdl:10398/8339
Keywords: 650